Evaluasi Kesesuaian Lahan pada Kawasan Tambak Marjinal di Kecamatan Suppa Kabupaten Pinrang - Ahmad Fahrizal (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2016)
This research aims to: Evaluate the suitabililty of land on which there are actual farms in marginal fishpond area at Wiringtasi, Tasiwalie, and Lotangsalo Villages, Suppa district, and Pinrang regency. Determining land suitability evaluation results based on the level of technology in the traditional cultivation, semi-intensive and intensive in marginal areas at the Wiringtasi, Tasiwalie, and Lotangsalo Villages, Suppa district, and Pinrang regency. This study uses primary and secondary data. Data collection is conducted by determining the research station randomized in the study site, water quality testing, both in-situ and laboratory testing. Methode of analysis using the analysis of Geoghrapich Information System (GIS). Land suitability classes are divided into classes S1 (Very appropriate), Class S2 (As appropriate), class S3 (Corresponding marginal) and the class N (Not applicable). The results of this study indicates that evaluation of the location of marginal fishpond land suitability study on approximately 46% of the rainy season leads to land suitability classes S3 and worth implementing technology-intensive cultivation, 44% of fishponds are int the S2 class by applying a semi-intensive aquaculture technologies, as weel as approximately 10% marginal fishponds in the S1 class with traditional aquaculture technologies. In dry season about 60% marginal fishponds research sites leads to the S3 or intensive classes, 35% of fishponds are in the class S2 or semi-intensive, and only about 5% of farms are in the class of S1 or traditional.